Topical preservative-free ophthalmic treatments: an unmet clinical need. (3rd June 2021) - Figus, Michele; Agnifili, Luca; Lanzini, Manuela; Brescia, Lorenza; Sartini, Francesco; Mastropasqua, Leonardo; Posarelli, Chiara
ABSTRACT: Introduction : The main role of preservatives in eyedrops is to ensure sterility and microbiological integrity of the drug, and to facilitate the penetration of active compounds into the eye. However, several studies documented significant toxic effects induced by preservatives, especially on the ocular surface. Consequently, most of the ophthalmic medications became progressively available in preservative-free (PF) formulations. Areas covered : We analyzed pre-clinical and clinical studies on PF eyedrops with particular attention to common chronic diseases such as dry eye and glaucoma. We discussed about the pros and cons of using PF eyedrops, in terms of efficacy, safety, and social-economic aspects. Expert opinion : There are still unresolved issues that make hard for PF medications to definitively conquer the drug market. Despite robust pre-clinical evidences of less toxicity, the low number of randomized clinical trials does not permit to state that PF eyedrops have, in clinical practice, a similar efficacy or a higher safety compared to preserved forms. These aspects limit their use to chronic diseases requiring long-term therapies with multiple daily instillations, especially in the presence of concomitant ophthalmic diseases that expose to a risk of ocular surface worsening.